1997
DOI: 10.1086/304095
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the X‐Ray–emitting Gas in the Hydra A Cluster of Galaxies

Abstract: The temperature and abundance structure in the intracluster medium (ICM) of the Hydra-A cluster of galaxies is studied with ASCA and ROSAT. The effect of the large extended outskirts in the point-spread function of the X-Ray Telescope on ASCA is included in this analysis. In the X-ray brightness profile, the strong central excess above a single β-model, identified in the Einstein and ROSAT data, is also found in the harder energy band (>4 keV). A simultaneous fit of five annular spectra taken with the GIS inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 38 publications
9
99
0
1
Order By: Relevance
“…This predicted evolutionary trend is well supported by the data on the analysis method used (e.g. Ikebe et al 1997;Markevitch et al 1998;White 2000). With some studies by means of the Italian-Dutch X-ray mission BeppoSAX some overview on the temperature structure of clusters was obtained, with decreasing temperature profiles outside ∼0.2r 500 and a diversity of the behavior in the core Vikhlinin et al 2006) and results obtained for a sample of clusters observed with XMM-Newton (right, Pratt et al 2007) region depending on the thermal history of the cluster (De Grandi and Molendi 2002).…”
Section: Figsupporting
confidence: 67%
See 1 more Smart Citation
“…This predicted evolutionary trend is well supported by the data on the analysis method used (e.g. Ikebe et al 1997;Markevitch et al 1998;White 2000). With some studies by means of the Italian-Dutch X-ray mission BeppoSAX some overview on the temperature structure of clusters was obtained, with decreasing temperature profiles outside ∼0.2r 500 and a diversity of the behavior in the core Vikhlinin et al 2006) and results obtained for a sample of clusters observed with XMM-Newton (right, Pratt et al 2007) region depending on the thermal history of the cluster (De Grandi and Molendi 2002).…”
Section: Figsupporting
confidence: 67%
“…The solid line shows the expected emission measure distribution for a 10 M year −1 isobaric cooling flow at solar metallicity, cooling from a temperature of 4.5-0.08 keV (Sanders et al 2008) It has to be noted that the interpretation of spectra from cooling flows had an interesting history already before the launch of Chandra and XMM-Newton. For example Ikebe et al (1997) and Makishima (1999) already argued on the basis of ASCA spectroscopy with similar arguments as those given above for M87, that the prediction of cooling flow models is not met by the observations. The counterargument to keep the cooling flow model alive at the time was to postulate internal absorption (see, e.g.…”
Section: Agn Heated Cluster Ccssupporting
confidence: 53%
“…Fabian et al 1997;Allen 2000;Allen et al 2001), or (2) an explanation of the spectra in terms of a two-temperature component model (e.g. Ikebe et al 1997Ikebe et al , 1999Makishima 2001) where the hot component is roughly equivalent to the hot bulk temperature of the clusters and the cool component corresponds approximately to T low . As actually pointed out e.g.…”
Section: The Interpretation Of Cooling Flow Spectra and Cluster Intrimentioning
confidence: 99%
“…Spectroscopic studies with ASCA provided evidence that there is at least more than one temperature phase present in cluster centers (e.g. Fabian et al 1994;Ikebe et al 1997Ikebe et al , 1999Makishima et al 2001). But these spectroscopic data obtained with ASCA are not sufficient to allow a detailed test of the cooling flow model by the reproduction of the predicted emission measure distribution as a function of temperature as predicted for the inhomogeneous cooling flow model (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The gas parameters for the Hydra A cluster are taken from Mohr & Evrard (1997), and the X-ray luminosity is provided by Ikebe et al (1997). The £rst detailed RM map of Hydra A was published by Taylor & Perley (1993), which exhibited very large RM values, especially for the south lobe of Hydra A.…”
Section: Appendix A: Individual Clustersmentioning
confidence: 99%